The Influence of Brand Image And Brand Love On Consumer Satisfaction Which Is Moderate By Word of Mouth At PT. POS Indonesia - Andreas Adi Mulyo; Laura Lahindah (Jurnal Riset Ekonomi Manajemen (REKOMEN), 2024)
This research aims to analyze the influence of brand image and brand love on PT consumer satisfaction. Pos Indonesia, as well as to test the moderating role of word of mouth in this relationship. This research was conducted on consumers of PT services. Indonesian post. The population in this study is unknown, so the researcher uses a reference from Hair et.al (2010) which states the minimum number of unknown samples is 100-200, so the sample in this study is 200. The sampling technique uses simple random sampling. Sampling was carried out by distributing questionnaires to consumers who came to the POS Indonesia office by providing a Google form link which was distributed to respondents. Partial Least Square (PLS) model analysis was used in this research. The results of this research are that brand image influences consumer satisfaction, brand love influences consumer satisfaction, word of mouth moderates brand image on consumer satisfaction and word of mouth moderates brand love on consumer satisfaction.